Exchange rate regime, exchange rate variability and flows of Malaysia's foreign trade - Niaz Ahmad, Mohd Naseem; Tan, Hui Boon; Mohd, Siti Hamizah (Penerbit Universiti Kebangsaan Malaysia, 2010)
This article empirically evaluates Malaysian foreign trade effects through two types of exchange rate variability; misalignments and volatility across different exchange rate regimes from 1991:Q1 to 2003:Q4. The Natural Real Exchange Rate (NATREX) equilibrium model is employed to generate the real exchange rate misalignment while the GARCH (1, 1) model is used to measure the real exchange rate volatility, which is then tested in a model of Malaysian imports and exports. This paper differs from existing literature as the effects of exchange rate misalignment significantly hastened the level of Malaysian exports and imports for the periods, managed floating and pegged rate. On the other hand, the exchange rate volatility has merely promoted the Malaysian exports and imports during the implementation of pegged rate. This proposes that the variability of exchange rate and exchange rate regimes are important determinants in inspiring Malaysian foreign trade, especially during the 1997 financial crisis when the economic is distressed.